Traditional apprenticeship in Ghana and Senegal: Skills development for youth for the informal sector - Sonnenberg, K (Journal of International Cooperation in Education, 2012)
The demographic youth bulge, representing large cohorts of youth, coupled with lack of pathways to education and employment and therefore social mobility, have become issues of great concern. As a result, youth employment and technical and vocational skills development have grown in prominence on international and national agendas in recent years. However, skills development strategies often overlook the informal sector despite the fact that in developing countries, income-generating activities in the informal sector often far exceed those of the formal sector. UNESCO’s 2012 EFA Global Monitoring Report on youth skills development states that traditional apprenticeships are an important way of acquiring transferable and job-specific skills, particularly for the informal sector. An extensive review of the literature of Ghana and Senegal reveals that these two countries have long histories of traditional apprenticeship and that these forms of skills training reach more youth than formal technical and vocational training. This paper examines the approaches these two countries’ governments have taken to increase access to and quality of non-formal skills training opportunities. Despite a lack of data on the long-term outcomes of these initiatives, programs and reforms, several important implications arise from these countries’ experiences. These implications are discussed as well as areas for future research.
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; A:West Africa; C:Senegal; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; HDR25; P:agriculture; P:measurement; Q:ICT; T:Ausbildung; T:Formal apprenticeship; T:Lehrlingsausbildung; T:apprentice; T:education and skills training; _C:Ghana GHA; publicImportV1; ⛔ No DOI found